Pendidikan Karakter dan Moderasi dalam Bingkai Asrama: Studi Kasus di SMP Ali Maksum Yogyakarta: Penelitian Kualitatif Studi Kasus - Ahmadan Haquridha Yasyada, Ahmadan; Muhammad Wasith Achadi; Liza Jauharotul Munfarida Al Khurriyyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character and Moderation Education have become key focuses in Indonesia’s educational system, especially in the era of globalization which influences the values of the younger generation. This study aims to explore the implementation of character and moderation education within the school and boarding environment at SMP Ali Maksum Yogyakarta. This research employs a qualitative method with a case study approach, involving in-depth interviews and observations of educational practices at the school and dormitory. The findings reveal that SMP Ali Maksum integrates character education through religious programs (diniyyah) and daily activities such as the 3S program (Smile, Greet, Salute), which aim to foster religious and moderate attitudes. The program involves collaboration among teachers, the student organization (OSIS), and the Class Representative Council (MPK) to ensure effective implementation. Regular evaluations are conducted to assess program success and identify challenges, such as the decline in positive habits during school holidays. Despite these obstacles, the intended outcome is the formation of students with strong character and moderate attitudes. This study provides a comprehensive overview of the role of boarding schools in promoting character and moderation education, as well as the importance of continuity in values taught both at school and within the family environment.